(untitled) (DARYAFT, 2025)
Women writers have significantly enriched the Urdu travelogue tradition by offering critical insights into religion, culture, politics, and gender relations. Pakistani women’s travelogues reveal shifting patterns of women’s rights across different societies and highlight the ways in which religion shapes women’s social status, autonomy, and equality. While cultural norms and religious interpretations can facilitate empowerment, they can also impose constraints on women’s lives. This study analyzes the impact of religion on women across diverse societies and examines religious exploitation as well as women’s varied experiences within religious and cultural traditions as represented in Pakistani women’s travelogues. Using these texts as primary sources, the research employs a feminist qualitative content analysis grounded in feminist theoretical frameworks. The findings indicate that some women perceive religion as a source of protection, identity, and spiritual comfort, whereas others experience it as a barrier to personal freedom and equal rights. The study concludes that religion’s influence on women’s lives is shaped by its interpretation and socio-cultural context, resulting in diverse gendered outcomes. Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified. Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies. Participant Consent: The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained.